Avaliação do uso do dispositivo intrauterino com liberação de levonorgestrel no controle do sangramento uterino anormal em pacientes com doença hemorrágica hereditária - Rayana Rolla Campos (2019)
Menorrhagia is defined as increased menstrual blood loss that interferes in women’s physical, emotional and social life. Quantitatively, it is defined as a blood loss which lasts more than seven days or which causes loss of more than 80ml of blood in a menstrual cycle. However, a quantitative evaluation of this bleeding is difficult to be assessed, although there are some evidences, such as blood that is not completely absorbed by a menstrual pad or a tampon, which leaked within one hour of use; and colored patient's clothes, history of iron-deficiency anemia, and low ferritin levels. Another way to diagnose is to perform the pictogram, a semi-quantitative method validated for evaluation of menorrhagia in which a score above 100 indicates an increased blood loss. Menorrhagia is one of the most important clinical manifestation of bleeding in women with hereditary hemorrhagic disorders (HHD). Purpose: To evaluate the efficacy of the levonorgestrel-releasing intrauterine device (LNG-IUD) in reducing uterine bleeding in patients with HHD, its effect in quality of life. Methods: Prospective clinical study. The study included patients diagnosed with HHD that had menorrhagia according to the pictogram for evaluation of bleeding. Tests for evaluation of hematimetric levels and iron kinetics and the Short Form 36 (SF-36) were applied. The patients were observed and had medical consultations one, three and six months after the LNG-IUD insertion (Mirena®, Bayer HealthCare pharmaceuticals Inc., Wayne, NJ, EUA). An endovaginal ultrasonography was performed 1 month after the insertion; the pictogram was collected again 3 months after the insertion; 6 months after the insertion, the SF-36 questionnaire, the laboratory tests and the pictogram were re-applied. Results: Twenty-two patients with HHD were included with LNGIUD inserted. Of these number, there were two lost to follow-up (one patient did not return and another had the IUD expelled). Six months later, a significant reduction in the volume of menstrual bleeding was observed, with a reduction of the pictogram’s punctuation from 407 in the pretreatment to 8.3 six months later (p<0.001) with 75% of the cases with amenorrhea. There was no significant statistical difference in hemoglobin and serum ferritin levels, but there was a significant increase in serum iron levels (the mean was 73.7 in the pre-treatment and 101.3 six months later; p=0.003). Regarding the evaluation of the quality of life, there was a significant improvement in all parameters of the SF-36 questionnaire. Conclusion: The LNGIUD is a safe and effective method to reduce menorrhagia in patients with HHD and in the improvement of quality of life.